2017
DOI: 10.1038/s41598-017-10602-9
|View full text |Cite
|
Sign up to set email alerts
|

MRI and Additive Manufacturing of Nasal Alar Constructs for Patient-specific Reconstruction

Abstract: Surgical reconstruction of cartilaginous defects remains a major challenge. In the current study, we aimed to identify an imaging strategy for the development of patient-specific constructs that aid in the reconstruction of nasal deformities. Magnetic Resonance Imaging (MRI) was performed on a human cadaver head to find the optimal MRI sequence for nasal cartilage. This sequence was subsequently used on a volunteer. Images of both were assessed by three independent researchers to determine measurement error an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…Visscher et al demonstrated that 3D printing alar cartilages using MRI showed a mean error of 2.5 mm. 107 Interestingly, most of the difference was found in 3D printing the medial crus but the lateral crus remained highly accurate, probably due to its more linear shape. Recently, Choi et al 3D-printed a patient-specific negative mould from CT to create silicone nasal implants for augmentative rhinoplasty using in-house software 108 and demonstrated a mean accuracy of 0.07 mm (0.17%) with no complications.…”
Section: Cartilage Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…Visscher et al demonstrated that 3D printing alar cartilages using MRI showed a mean error of 2.5 mm. 107 Interestingly, most of the difference was found in 3D printing the medial crus but the lateral crus remained highly accurate, probably due to its more linear shape. Recently, Choi et al 3D-printed a patient-specific negative mould from CT to create silicone nasal implants for augmentative rhinoplasty using in-house software 108 and demonstrated a mean accuracy of 0.07 mm (0.17%) with no complications.…”
Section: Cartilage Modellingmentioning
confidence: 99%
“…Recently, Choi et al 3D-printed a patient-specific negative mould from CT to create silicone nasal implants for augmentative rhinoplasty using in-house software 108 and demonstrated a mean accuracy of 0.07 mm (0.17%) with no complications. 51 Chae et al, 63 Garcia-Tutor et al, 64 Gillis et al, 102 Mehta et al, 103 Suarez-Mejias et al, 104 Cabalag et al, 105 Taylor et al, 106 Visscher et al, 107 Choi et al, 108 Chae et al 136 Source: Cohen et al, 66 Bosc et al, 109 Ganry et al, 110 Liang et al, 111 Mottini et al, 112 Schouman et al, 113 Seruya et al, 114 Rohner et al, 115 Saad et al, 116 Hanasono et al, 117 Ciocca et al, 118 Infante-Cossio et al, 119 Zheng et al, 120 Hou et al, 121 Antony et al, 122 Leiggener et al 123…”
Section: Cartilage Modellingmentioning
confidence: 99%
“…The resolution of micro-CT is much higher than that of ordinary CT, with the cross-sectional pixel size reaching the micron level, which can improve the localization and morphological visualization of the nasal cartilage. Visscher et al 20 did not reconstruct the nasal cartilage structure with CT, but applied micro-CT to verify the effect of cartilage modelling (Fig. 2).…”
Section: Computerized Tomographymentioning
confidence: 99%
“…Its most significant advantage is that it can rebuild each patient-specific nasal cartilage structure based on individual patient data. Visscher et al 20 created a cartilage reconstruction model by scanning the nasal tissue of a corpse after fixation. Our team used MRI for the first time to scan the nasolabial part of healthy individuals and patients with unilateral cleft lip and nose deformities, reconstructed the cartilage structure of the nose and designed surgery based on the cartilage structure.…”
Section: Computerized Tomographymentioning
confidence: 99%
See 1 more Smart Citation